Amniotic membrane graft to patch an overfiltering trabeculectomy flap - Michael C. Yang; Michelle T. Sun; Wendy W. Liu (American Journal of Ophthalmology Case Reports)
Purpose: To describe the use of an amniotic membrane graft (AMG) with fibrin sealant to address an overfiltering trabeculectomy flap encountered intraoperatively. Observations: A 35-year-old female with severe primary open angle glaucoma underwent trabeculectomy with mitomycin C due to uncontrolled intraocular pressure (IOP). Intraoperatively, the elastic nature of the scleral flap led to overfiltration, causing persistent anterior chamber shallowing despite numerous sutures. To decrease but not completely shut down aqueous outflow through the trabeculectomy flap, we utilized AMG and fibrin sealant to stabilize the flap. Postoperatively, the patient had a formed anterior chamber, elevated bleb and significantly reduced IOP, without the need for additional glaucoma medications. Conclusions and importance: Amniotic membrane grafts (AMG) with fibrin sealant may help regulate aqueous flow efflux, maintain anterior chamber stability, and mitigate the risk of postoperative hypotony in trabeculectomy surgery. AMG was chosen in this setting given its anti-inflammatory, anti-fibrotic properties, as well as its optically clear nature to allow for post-operative visualization of the flap. AMG allows for early postoperative stabilization of the scleral flap without complete obstruction, and may be useful in patients at risk of early postoperative hypotony.